2017
DOI: 10.1021/acs.jpcb.7b03683
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of H2S Release in Reactions of Diallyl Polysulfides with Thiols

Abstract: Hydrogen sulfide (HS) is a gasotransmitter molecule recognized for its role in cell signaling. Garlic-derived polysulfides including diallyl disulfide (DADS) and diallyl trisulfide (DATS) have been shown to release HS. We investigated the mechanism of the reaction of DADS and DATS with biological thiols, including cysteine (Cys) and glutathione (GSH), using density functional theory. We propose that Cys and GSH react with DADS and DATS in their anionic forms. Thiol anions are much more likely to attack the sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…It has to be noted that the mechanisms by which H 2 S is released from DATS have in depth analyzed by several research groups ( 22 , 39 42 ). In particular, it has been shown that H 2 S is liberated from DATS in presence of GSH and l -cys ( 43 ). However, sulfane sulfur (polysulfides), rather than H 2 S, are considered the active agent in physiological signaling ( 44 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted that the mechanisms by which H 2 S is released from DATS have in depth analyzed by several research groups ( 22 , 39 42 ). In particular, it has been shown that H 2 S is liberated from DATS in presence of GSH and l -cys ( 43 ). However, sulfane sulfur (polysulfides), rather than H 2 S, are considered the active agent in physiological signaling ( 44 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…ASH can be generated by nucleophilic attack of the cellular thiol at the central S-atom of DAS3 (Scheme 2, path-a), whereas reaction at either of the peripheral S-atoms would generate AS2H (Scheme 2, path-b). Previous computational calculations predict that thiol-polysulfane exchange reactions at the peripheral S-atoms of DAS3 are kinetically more favourable [38]. However, only ASH production is observed in B. subtilis when exposed to DAS3.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…These effects are believed to be mediated by physiological concentrations of H 2 S. Therefore, H 2 S is now regarded as a third gaseous signaling molecule, next to nitric oxide (NO) and carbon monoxide (CO). In order to develop H 2 S-releasing donors, researchers started to modify chemical structures of well-described sulfide releasing agents, obtaining several H 2 S donors including Lawesson's reagent and analogues [8], DTT (1,2-dithiole-3-thiones) derivatives like ADT-OH, ACS 5, ACS 48 and ACS 50 [9][10][11], diallyl disulfide (DADS) derivatives like ACS 81 [12], arylthioamides (TBZ) [13], aryl isothiocyanates [14] and thiourea derivatives [15] (Figure 1). Interestingly, there are numerous well-established medicines which contain sulfur moieties.…”
Section: Hydrogen Sulfide In Physiology and Pharmacologymentioning
confidence: 99%